DISTRIBUTION OF LOGISTICS TO THE COMMUNITY OF SAPTA MARGA DESA, MANYAK PAYED KECAMATAN, ACEH TAMIANG KABUPATEN - Muhammad Khatami; Ferdian Syatrio; Munis Yasar; Reizky Aditya; Li Idi'il Fitri; Abdur Rahman Hakim; MUh Rifai Arsyad (Jurnal Masyarakat Berdikari dan Berkarya (Mardika), 2025)
This Community Service (PKM) activity aims to improve the effectiveness of logistics management and distribution in Sapta Marga Village, Manyak Payed District, Aceh Tamiang Regency, by providing three portable racks. The implementation method included a needs survey, program planning, facility procurement, implementation, outreach, and monitoring and evaluation. The results showed that the portable racks improved storage tidiness, facilitated inventory collection, and accelerated aid distribution to the community. The program also increased village officials' understanding of more organized and efficient logistics management.